Hedging and competition - Liu, Tingjun; Parlour, Christine A. (Journal of Financial Economics, 2009)
We consider firms that, all else equal, wish to minimize variability in their internal capital (due to convex costs of raising external funds). The firms can hedge the cash flow risk of the project, but not that of winning or losing the auction. We characterize optimal hedging and bidding strategies in this competition framework. We show that access to financial markets makes firms bid more aggressively, possibly even above their valuation for the project. In addition, hedging increases the variance of bids and makes firm values more dispersed. Further, with hedging, the covariance of internal capital changes with the risk factor is negative, and is more negative, the higher the correlation of the hedging instrument with the risk factor.